Target Organ Complications and Cardiovascular Events Associated with Masked Hypertension and White Coat Hypertension: Analysis from the Dallas Heart Study - Tientcheu, Danielle (J Am Coll Cardiol, 2015)
BACKGROUND: Multiple epidemiological studies from Europe and Asia have demonstrated increased cardiovascular risks associated with isolated elevation of home blood pressure (BP) or masked hypertension (MH). Previous studies have not addressed cardiovascular outcomes associated with MH and white coat hypertension (WCH) in the general population in the United States. OBJECTIVES: The goal of this study was to determine hypertensive target organ damage and adverse cardiovascular outcomes associated with WCH (high clinic BP ≥140/90 mm Hg, normal home BP of <135/85 mm Hg), MH (high home BP ≥135/85 mm Hg, normal clinic BP <140/90 mm Hg), and sustained hypertension (SH, high home and clinic BP) in the Dallas Heart Study, a large, multiethnic probability-based population cohort. METHODS: We evaluated associations between WCH, MH, SH and aortic pulse wave velocity (APWV) by magnetic resonance imaging; urinary albumin to creatinine ratio (UACR); and cystatin C at study baseline. Then, associations between WCH and MH with incident cardiovascular outcomes (coronary heart disease, stroke, atrial fibrillation, heart failure, and cardiovascular death) over a median follow-up period of 9 years were assessed. RESULTS: The study cohort comprised 3,027 subjects (50% African Americans). The sample-weighted prevalence of WCH and MH were 3.3% and 17.8%, respectively. Both WCH and MH were independently associated with increased APWV, cystatin C, and UACR. Both WCH and MH were independently associated with higher cardiovascular events compared with the NT group, even after adjustment for traditional cardiovascular risk factors (adjusted HR: 2.09; 95% CI: 1.05 to 4.15 and adjusted HR: 2.03; 95% CI: 1.36 to 3.03, respectively). CONCLUSIONS: In a multiethnic U.S. population, both WCH and MH were independently associated with increased aortic stiffness, renal injury, and incident cardiovascular events. Because MH is common and associated with an adverse cardiovascular profile, home BP monitoring should be routinely performed among U.S. adults.